STRUKTUR TAHANAN ALIRAN TURBULEN DI ATAS PERMUKAAN KASAR DASAR SALURAN TERBUKA - Sukarno, - (JURNAL ILMIAH MEDIA ENGINEERING, 2013)
Effect of regularly arrayed sphere and cylindrical roughness on flow resistance and turbulent structures at over completely rough-bed with uniform stainless steel rods, and glass beads in an open channel have been investigated. Detail measurement of flow depth were conducted by using Particle Image Velocimetry. Experimental results indicated that flow resistance with sphere roughness is stronger than cylindrical roughness. Significant degrees of spatially regular variation in the time-average velocity were generated along the rough element in case of the large ratio of the roughness height to flow depth. In addition, Reynold shear stress abruptly decreased near the ridge of roughness elements. It was suggested that the difference in flow resistance between sphere roughness and cylinder one, these organized flow structure were explained by form induce stressKeywords: open-channel shallow flow, flow resistance, rough-bed, turbulent characteristic, PIV.